Modified Hughes Tarsoconjunctival Flap Procedure for Lower Eyelid Defect: Poster Presentation - Case Series - Resident - aulia; hendriati; mardijas efendi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Hughes procedure of tarsoconjunctival flap is a method of choice in reconstructing full thickness inferior eyelid defect that involves >50% of eyelid margin to restore anatomical integrity, function, and cosmetic of the eyelid. The modified Hughes procedure includes sparing of the marginal upper lid tarsus and removal of the levator muscle aponeurosis from the tarsoconjunctival flap.This article reports 2 patients who underwent modified Hughes procedure after basal cell carsinoma excision. Case Illustration : Two patients underwent inferior eyelid reconstruction using modified Hughes procedure. After wide excision of the tumor, tarsoconjunctival flap was made to reconstruct posterior lamella of the eyelid. Subsequently, anterior lamella of the eyelid were reconstructed using full thickness skin graft and advancement flap, respectively. Both patient then underwent second surgery, tarsus flap release, 6-8 week after the first surgery. Discussion : A tarsoconjunctival flap from the upper eyelid replaces the posterior lamella, whereas a skin graft, a skin flap, or a skin-muscle flap restores the anterior lamella. After surgery, tarsal flap apposition, skin flap/graft, and stitches were intact. After tarsus flap release, wound healing was good. Tumor biopsy showed basal cell carcinoma. Conclusion : Modified Hughes procedure is a treatment of choice in reconstructing full thickness inferior eyelid defect involving >50% of eyelid margin. Full thickness skin graft and advancement flap to reconstruct anterior lamella of the eyelid is choosen after considering skin color and texture similarity and laxity of eyelid and cheek.